'An Alternate Conclusion of Misadventure': Construction of the Female Body in Rape Trial. Issue 1 (June 2021) - Joshi, Jayat
I aim to examine the discursive construction of the female body and the definitions of rape and consent in the language used in the Indian courtroom. In order to do so, I locate my analysis in two recent controversial judgements— Mahmood Farooqui v. State (Govt. of NCT of Delhi), 2017 and Vikas Garg and others v. State of Haryana, 2017 —both of which reveal how judicial discourse produces female (and male) bodies as normalized sites of a distorted sexuality. Further analysis shows the limitations of legal grammar and semantics in envisaging the female body outside of categories existing in relation to men, and the failure of the judicial apparatus when such classifications crumble. To develop this analysis, I chiefly draw upon the writings of scholars of legal feminism and a scrutiny of reports of the Law Commission of India. The purpose of this article is therefore to arrive at an understanding of the subject of the law as not merely a theoretical, objective entity but as a product of a gendered, variable ideological context, thereby exposing the weaknesses of the linguistic construction of the female body and how it affects decisions of the courts.